The Lion King animated storybook: A case study of aesthetic and economic power. - Ricker, Audrey (Critical Arts: A South-North Journal of Cultural & Media Studies, 1996)
Uses `The Lion King' animated storybook as a case study of aesthetic and economic power. Children's regarding of themselves as members of a stable, select social group that uses mass-mediated `words and images' to create and sustain social relationships; Interaction of children with the Disney diegesis; Aesthetic imperialism in the way children react to products by Walt Disney.